2017
DOI: 10.5334/ijic.2510
|View full text |Cite
|
Sign up to set email alerts
|

The Development, Description and Appraisal of an Emergent Multimethod Research Design to Study Workforce Changes in Integrated Care Interventions

Abstract: Introduction:In this paper, we provide a detailed and explicit description of the processes and decisions underlying and shaping the emergent multimethod research design of our study on workforce changes in integrated chronic care.Theory and methods:The study was originally planned as mixed method research consisting of a preliminary literature review and quantitative check of these findings via a Delphi panel. However, when the findings of the literature review were not appropriate for quantitative confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The latter includes those aspects that affect clinical and non-clinical staff involved in the intervention and are, for example, related to the changes experienced by the health workforce. The research design is reported in detail elsewhere [1223]. A description of the main elements of the data collection and analysis is provided in the following.…”
Section: Methodsmentioning
confidence: 99%
“…The latter includes those aspects that affect clinical and non-clinical staff involved in the intervention and are, for example, related to the changes experienced by the health workforce. The research design is reported in detail elsewhere [1223]. A description of the main elements of the data collection and analysis is provided in the following.…”
Section: Methodsmentioning
confidence: 99%
“…Because of their multifaceted nature, complex interventions must be studied from different angles, which requires the use of different data sources. However, the data collection and analysis from each of these sources might develop in unforeseen ways and their combination may therefore require changes to the research design throughout the different stages of its execution [ 24 ]). These changes can be accommodated most appropriately within the scope of a flexible and emergent design, that is, a design that evolves throughout its different stages and allows for the interaction between different strands of data at different points of time during the research [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study employed an emergent and interactive research design that included a literature review, empirical research via a qualitative expert questionnaire, and secondary analysis of two case reports. The research design has been described in detail elsewhere [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…They include a lack of clear, systematic understanding of integrated care among key stakeholders [8] and a lack of standardised, validated tools and indicators to measure integration [3]. Previous research also describes workforce challenges, including an existing, entrenched workforce culture, limited opportunities for cooperation and communication, interprofessional education, resistance to share care, high costs, staff skills and information technology systems [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Limited access to experts inhibits the scaling up of existing competencies and curricula [4]. Faculty expertise, financial, organisational and logistical factors are other recognised barriers to implementing integrated curricula into healthcare workers' training [15,10,11]. Training still emphasises the diagnosis and treatment of acute diseases, fragmented, outdated and static curricula, and education and practice that focus on component elements of an issue or disease [16].…”
Section: Introductionmentioning
confidence: 99%